Penerimaan Dana Ziswaf Dan Pendapatan Musyarakah Terhadap Piutang Murabahah BPR Syariah - Ahmad Rifqi; Suprihatin Lestari; Vanisa Meifari (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to examine the effect of ZISWAF fund receipts and Musyarakah income on Murabahah receivables in Islamic Rural Banks (BPR Syariah), with Firm Size as a moderating variable. This research employs a quantitative approach using secondary data obtained from the financial reports of BPR Syariah over a five-year period (2020–2024), sourced from the official OJK website, and selected through purposive sampling. The data were analyzed using the Panel Data Regression Model, followed by Moderated Regression Analysis (MRA). The model selection tests (Chow Test and LM Test) indicate that the Common Effect Model (CEM) is the most appropriate model for this study.